Analisis Korelasional antara Pemahaman Orang Tua tentang Pendidikan, Keterlibatannya dalam Aktivitas Pendidikan, dan Hubungannya Dengan Hasil Belajar Siswa - Muminah, Mimin (Tsamratul Fikri | Jurnal Studi Islam, 2016)
This research article found three conclusions as follows: (1) An understanding of parents on education (Variable X1) is associated very strongly with students learning outcomes (Variable Y) at Madrasah Ibtidaiyah in the District of Sadananya, Ciamis Regency. The better understanding of parents about the education, the better the learning outcomes of students. This conclusion is obtained based on the results of correlation using Pearson Product Moment Correlation Test, where the test resulted in a correlation coefficient of 0.969. (2) The involvement of parents in educational practice (Variable X2) is also associated very strongly with with students learning outcomes (Variable Y) at Madrasah Ibtidaiyah in the District of Sadananya, Ciamis Regency. This conclusion is derived from the results of correlation between two variables, where the figures obtained correlation coefficient of 0.946. (3) Two variables, namely the understanding of parents on education (Variable X1) and the involvement of parents in educational practice (Variable X2) is jointly associated very strongly with the students learning outcomes (Variable Y). It is derived from multiple correlation between the test results Variable X1 and X2 together with a variable Y, where the figures obtained multiple correlation coefficient of 0.972. Therefore, understanding parents about education and parental involvement in the education practice a very important role in improving the learning outcomes of students. ion coefficient of 0.752 (included in the category of very strong).